Pharmaceutical Pricing and Reimbursement Policies in Mexico - Moïse, Pierre (OECD Health Working Papers, 2007)
This paper examines aspects of the policy environment and market characteristics of Mexico's pharmaceutical sector, and assesses the degree to which Mexico has achieved certain policy goals. This paper questions the effectiveness of the maximum price regulation. It notes that retail prices for pharmaceuticals are relatively high, although proximity to the United States may have some influence. Although not wholly successful in containing overall drug expenditures, the federal government can claim some measure of success for the public sector market. A high reliance on out-of-pocket spending brings into question the sustainability of financing pharmaceuticals in Mexico. It also contributes to greater inequality, although a new health insurance scheme, the Seguro Popular, is addressing the latter with some success as it endeavours to provide coverage for the half of Mexico's population without health insurance. Finally, the paper acknowledges the government.s efforts in improving efficiency of expenditures and quality of care through new bioequivalency requirements for generics. However, an unintended side-effect of the loss of low cost, non-bioequivalent drugs may be higher average prices for pharmaceuticals